2015
DOI: 10.1007/s40520-015-0424-2
|View full text |Cite
|
Sign up to set email alerts
|

Densitometric evaluation of bone remodelling around Trabecular Metal Primary stem: a 24-month follow-up

Abstract: At the present time, DEXA is considered the most reliable tool for evaluating bone remodelling after THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…This has been observed by several authors of studies conducted with short stem implants. 29,34,35 As was observed in the current study, these bony alterations occurred within the first couple of months after implantation and then stopped, 2,31,[36][37][38] suggesting that it is an answer to changes in loading conditions. This questions the proximal fixation of this trochanter sparing short stem and leads to think that it may function more like a shorter straight stem with distal load transfer than a short stem with proximal load transfer.…”
Section: Discussionsupporting
confidence: 78%
“…This has been observed by several authors of studies conducted with short stem implants. 29,34,35 As was observed in the current study, these bony alterations occurred within the first couple of months after implantation and then stopped, 2,31,[36][37][38] suggesting that it is an answer to changes in loading conditions. This questions the proximal fixation of this trochanter sparing short stem and leads to think that it may function more like a shorter straight stem with distal load transfer than a short stem with proximal load transfer.…”
Section: Discussionsupporting
confidence: 78%
“…Due to the limited evidence retrieved on BMD measurements in lower limb amputees rehabilitated using OI, a supplementary table was generated to summarise studies reporting BMD measurements in patients who received an osseointegrated prosthesis for hip or knee joint replacement procedures (THA and TKA; Table SII). Many of these supplementary studies on both THA and TKA reported an overall decrease in BMD for all measured regions of interest (ROIs) (30)(31)(32)(33)(34)(35). In addition, others found variations in BMD changes from no change to decreased BMD post-surgery in different ROIs (36,37).…”
Section: Bmd Measurements For Oi In Amputeesmentioning
confidence: 99%
“…The value MRI can add to BMD is that it can predict the strength of cancellous bone in addition to the bone quality change [14]. It is worth mentioning that BMD can be assessed using dual energy X-ray absorptiometry (DEXA) which was reported to be the most accurate and reliable technique for the assessment of BMD [15]. Qualitative and quantitative information that can be used for Finite Elements Analysis [16] Another view to consider is the suggestion, made by Porrelli et al [16], that morphological information cannot be extracted from DEXA and ultrasonography alone in a qualitative and quantitative manner.…”
Section: Diagnostic Toolsmentioning
confidence: 99%